Exploring Divisional Vs. Managerial Performance Evaluation Practices in Listed Companies: Evidence from Sri Lanka - Indrani, M.W.; Naidoo, M.; Wickremasinghe, G. (International Journal of Accounting & Business Finance, 2020)
Businesses have become more and more widespread and diverse and, thus tend to apply strategies i.e. decentralization to improve the performance while securing long term growth. The main objective of this study is to provide with a comparative analysis of divisional vs. managerial performance evaluation (PE) practices of listed companies in Sri Lanka, focusing on common measures and owned KPIs, and allied purposes. This study applies Mixed Method Research (MMR) approach. Data were gathered through a questionnaire survey and discussions with financial executives of 42 listed companies representing five industry sectors. Facilitating with SPSS software, quantitative data were analyzed using frequency tables and Fisher’s exact test, and thematic analysis and content analysis were applied for qualitative data.The findings reveal that almost all companies evaluate both divisional and managerial performance to achieve multiple purposes, agreeing to controllability principle and mostly compared with budgeted outcome showing its soundness and popularity in this function. Determining separate units/ divisions for PE largely depends on specific situations, nature of businesses, operations and markets dealt with (i.e. Plantation sector), and attitudes of management. With regard to the importance of measures surveyed, no differences appear between divisional and managerial PE, and more concern goes to measures that reflect divisional contribution like sales volume, divisional net profit before taxes and contribution margin than EVA, ROI, and ROS. Given that the deficits of common measures, it suggests establishing owned KPIs for individual companies and modifying them as and when required to evaluate real performance effectively. Better performance would follow if this was complemented by rewards or penalties. The findings add to the understanding on the appropriateness of bases used for creating divisions and of applying common measures and owned KPIs for PE function of different companies /industry sectors and also on complications faced with specific business/industry settings on the above concern. It also provides motivations for employees particularly for divisional managers to achieve higher performance with job satisfaction and rewards, and hence uplifting living conditions and social status too. Overall, the findings would help organizations in both developing and developed economies to establish and improve PE systems to their divisions/ branches towards achieving intended purposes successfully.
Keywords: Listed companies; Industry sectors; Performance evaluation; Divisional vs. managerial performance; KPIs